IDENTIFIKASI DEGRADASI TANAH DAN PENGARUH FAKTOR PENGGUNAAN LAHAN TERHADAP DEGRADASI TANAH PADA KEBUN CAMPURAN DAN SEMAK BELUKAR DI KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT PROPINSI MALUKU - Silwanus M Talakua (Universitas Pattimura, 2016)
Soil degradation on shrubbery is higher than the mixed planting with indicators of soil degradation are pedestal, root plant exposure, rill and gully. Individually, the extent of land use, the density of upper vegetation and the density of lower vegetation have significant effects on the soil degradation at mixed plantation and shrub. Simultaneously, the extent area of land use, the density of upper vegetation and the density of lower vegetation have significant effect on the soil degradation at mixed plantation and shrubbery. The factors that have the greatest effect on the soil degradation at mixed plantation are the extent area of land use and density of lower vegetation, meanwhile those factors in the shrubbery are the density of upper and lower vegetation.